Report of the committee of distribution to relieve soldiers' families : December 18, 1864 (Document (Virginia. General Assembly. Senate) ;, 1864)
December 18, 1864 Report from the committee of distribution to relieve soldiers' families who are living within the lines or under the control the the United States forces, including some interpretation of when payments should be made; transmitted by Henry W. Thomas, President Board of Commissioners, from the Second Auditor's Office.